Personnel protection : executive compensation and fringe benefits, proven practices - Miller, Jerome (Elsevier, 2013)
According to IRS code, any property or service that an executive receives in lieu of or in addition to regular taxable wages is a fringe benefit that may be subject to taxation. There are exceptions to this rule, however, which may include security services provided. In Personnel Protection: Executive Compensation and Fringe Benefits, the factors necessary to exclude security-related expenses from the executive's taxable gross income are defined, and the benefits to both the executive and the company are discussed.